The Psychology of Dictatorship: A Journey into Muammar Gaddafi's Mind in Yasmina Khadra's The Dictator's Last Night. Issue 2 (15th March 2023) - Senoussi, Mohammed
ABSTRACT: This article anatomizes the depiction of the dictator's mind-set and psyche in Yasmina Khadra's The Dictator's Last Night (2015) . Using the first person, Khadra attempts to give an inside insight into the mind of Colonel Muammar Gaddafi of Libya, one of the most colorful, controversial and complex figures of recent history. The selected novel broadens our understanding by offering a psychiatric diagnosis of the dictator. This paper thus explores how the author delves into the dictator's mind mapping literary psychopathology of Gaddafi's personality through realistic reconstructions. In other words, we attempt to explain how the dictator manifests the symptoms of one who is trapped in a destructive state of mind using the novel as a focal point and guide. The paper tries to put flesh on the bones of questions concerning Gaddafi's mind-set and absolute power wedded to madness and megalomania as well as reflecting upon certain images and symbols utilized to show historically or in mythic form the hyperbolic figure of the dictator that forms the central theme in the novel. To make the journey inside the dictator's mind possible, the article uses a psychoanalytic approach and refers to historical facts to back up the results.